REVEALS reconstruction of past vegetation cover with original RPP values for European samples - Herzschuh, Ulrike; Ewald, Peter; Schild, Laura; Li, Chenzhi; Böhmer, Thomas (PANGAEA, 2023)
This data set presents the reconstructed vegetation cover for 3491 sites based on harmonized pollen data from the data set LegacyPollen 2.0 (https://doi.pangaea.de/10.1594/PANGAEA.929773). 1115 sites are located in North America, 1435 in Europe, 533 in Asia, 173 in South America, 155 in Africa, and 80 in the Indopacific. Sugita's REVEALS model (2000) was applied to all pollen records using REVEALSinR from the DISQOVER package (Theuerkauf et al. 2016). Pollen counts were translated into vegetation cover by accounting for taxon-specific pollen productivity and fall speed. Additionally, relevant source areas of pollen were calculated using the aforementioned taxon-specific parameters and a gaussian plume model for deposition and dispersal. Values for relative pollen productivity and fall speed from the synthesis from Wiezcorek and Herzschuh (2010) were used for the reconstruction of vegetation cover. The average values from all Northern Hemisphere values were used where taxon-specific continental values were not available. This includes records of the Southern Hemisphere. We present tables with reconstructed vegetation cover for all continents with original parameters. As further details we list a table with the taxon-specific parameters used and a list of parameters adjusted in the default version of REVEALSinR.
Keywords: fossil pollen; paleoecology; REVEALS